Development Strategy of Farmer Group Institution in Rice Farming in Takalar - Jumiati; Hamzah, Ismayanti; Nadir; Akbar; Molla, Saleh (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2025)
Farmer group institutions play an essential role in community life because they allow farmers to work together to solve problems such as the fulfillment of agricultural inputs, cultivation, and marketing of farm products. This study aimed to identify internal and external factors affecting institutional development in rice farming and formulate development strategies to strengthen the institution and maximize its role in rice farming. The data analysis used in this research is qualitative descriptive with SWOT. Internal factors that become strengths are strategic land location, quality agricultural products, financial management carried out optimally, trained and experienced farmer group members and means of sales promotion. Internal factors that become weaknesses are the low responsibility of farmer group members, limited capital, incomplete agricultural production facilities, and direct sales of farm products to intermediary traders/intermediaries. External factors that become opportunities are government assistance, counseling from agricultural institutions, technological developments, population, and good relations with communities that support farmer group activities. Threat factors are erratic weather, unsafe environment, government programs that are still project-based, and weak program coordination between institutions. Alternative strategies that can be carried out in developing farmer groups are increasing the quantity and ability of farmer group members by participating in training activities to the fullest and utilizing land use, increasing agricultural production facilities through government assistance, and maintaining good relations with the dynamics of extension groups and organizations, maximizing the potential or experience possessed by farmer group members in improving coordination between institutions, and maximizing the role of agricultural extension.